Evaluación del efecto del péptido sintético Pb53A derivado de toxinas de la araña Phoneutria boliviensis sobre la viabilidad celular de la línea HEK293 (2021)
Cerebral ischemia is caused by the obstruction of a blood vessel in the brain and is generated by a hypoxic depolarization resulting from the influx and elevation of intracellular free calcium from the extracellular space and the endoplasmic reticulum. This excessive influx of calcium into hypoxic cells induces the activation of apoptotic processes that kill neuronal activity. The use of peptide toxins of animal origin is of great importance in modulating the activity of the NMDA receptor, which is associated with the excitotoxic phenomenon resulting from the increase in intracellular calcium concentration; an example is the Phoneutria boliviensis peptide toxins that show high homology with Phoneutria nigriventer peptide toxins that interact with the GluN2B subunit of the NMDA receptor. In this document we present the study of the cytotoxic effect that these peptides exert on the adherent eukaryotic cell line HEK-293, by means of the assay of the metabolic reduction of 3- (4,5-dimethylthiazol-2-yl) -2,5- bromide diphenyltetrazolium (MTT), as a preliminary assay for the evaluation of this peptide in the regulation of NMDAR receptor activity. The results obtained allow us to suggest that the peptide tested (Pb53a) does not have a significant effect on the decrease in cell viability of the HEK-293 line in a concentration range from 1 µM to 500 µM and therefore it can be used in assays of the functional evaluation of the NMDA receptor.